2014
DOI: 10.1186/1472-6882-14-397
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antioxidant properties of active principals isolated from water hyacinth against four cancer cells lines

Abstract: BackgroundEichhornia crassipes (Mart) solms is an invasive macrophyte causing serious problems to the network of irrigation and drainage canals in the Nile Delta region. The present study aim to evaluate the potential anticancer and antioxidant activities of Eichhornia crassipes crude extract and its pure compounds.MethodsThe macrophyte was collected from El-Zomor canal, River Nile (Egypt), cleaned, air dried, grinded then extracted with methanol (crude extract). The extract was fractionated using pre-coated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…During the latest 20 years, the mechanism by which continued oxidative stress can lead to chronic inflammation—which could in turn mediate various diseases including cancer—was revealed [31]. Moreover, experimental studies (both in vitro and in vivo), demonstrated the role of plant natural compounds on growth inhibition of cancer cells [31,32,33,34]. Cytotoxic effects were also ascribed to the phenolics whose biological functions are, however, related to their structure.…”
Section: Resultsmentioning
confidence: 99%
“…During the latest 20 years, the mechanism by which continued oxidative stress can lead to chronic inflammation—which could in turn mediate various diseases including cancer—was revealed [31]. Moreover, experimental studies (both in vitro and in vivo), demonstrated the role of plant natural compounds on growth inhibition of cancer cells [31,32,33,34]. Cytotoxic effects were also ascribed to the phenolics whose biological functions are, however, related to their structure.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that tiliroside has cytotoxic activities on T47D and MCF7 with IC 50 values of 67.79 and 112.77 µg/ml, respectively. Based on the study by Aboul-Enim et al, [15] these activities were classified as weak activity, but other researchers classified them as moderate. [16] Based on IC 50 value, it was observed that tiliroside has a low cytotoxic activity on MCF7 cell lines.…”
Section: Cytotoxic Activity Assessment Of Tiliroside On T47d and Mcf-mentioning
confidence: 99%
“…Sequential fractionation of active extracts with organic solvents, for example, petroleum ether, acetone, dichloromethane, ethyl acetate, butanol and methanol (Khlifi et al 2013;Tagne et al 2014) has also been reported. The cytotoxicity assay most widely used for estimating the anticancer potential of EFM is the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Babykutty et al 2008;Fan et al 2014;Liu et al 2014;Park et al 2005), but other assays such as the sulphorhodamine B (SRB), neutral red, and lactate dehydrogenase (LDH) leakage assays have also been used (Aboul-Enein et al 2014;Prasad et al 2005;Rose et al 2005). The MTT assay gives an indication of whole cell cytotoxicity.…”
Section: Common Experimental Approachesmentioning
confidence: 98%
“…Flow cytometric analysis, apoptosis-specific assays (i.e., acridine orange/ethidium bromide staining; annexin/propidium iodide staining), mitochondrial membrane potential visualization assay, DNA fragmentation assay, gene expression analysis, reverse transcription-polymerase chain reaction (RT-PCR) assay, and Western blot analysis have been used to study the induction of apoptosis by extracts and compounds isolated from EFM (Aboul-Enein et al 2014;Babykutty et al 2008;Chen et al 2014;Dwarka 2012;Engel et al 2014;Hussin et al 2014;Zhang et al 2013b). Instrumental analyses such as reversed-phase high performance liquid chromatography (RP-HPLC), gas chromatography (GC), mass spectrometry (MS), infrared (IR) and nuclear magnetic resonance (1D and 2D NMR) (Boyd et al 2006;Fan et al 2014;Ooh et al 2014) were used to detect, characterize, and identify potential anticancer compounds from EFM.…”
Section: Common Experimental Approachesmentioning
confidence: 99%